We are 'Truly Asia' indeed - Abd Razak, Dzulkifli (2008)
WITH the recent celebration of Chinese New Year, Malaysia once again reaffirmed its commitment towards a multicultural society. Reportedly, overall, this year's celebration seemed merrier than before. In Kuala Terengganu, in particular, it is claimed that for the first time leaders of other communities tossed "Yee Sang", the mixture of raw fish and vegetables, a dish costing RM888, aptly to signify prosperity. The festive atmosphere in Malaysia was a contrast to the north of our border, where I happened to be during the eve of the Lunar New Year. The mood was more demure.